2016
DOI: 10.1038/srep31618
|View full text |Cite
|
Sign up to set email alerts
|

Native cellulose nanofibrills induce immune tolerance in vitro by acting on dendritic cells

Abstract: Cellulose nanofibrills (CNFs) are attractive biocompatible, natural nanomaterials for wide biomedical applications. However, the immunological mechanisms of CNFs have been poorly investigated. Considering that dendritic cells (DCs) are the key immune regulatory cells in response to nanomaterials, our aim was to investigate the immunological mechanisms of CNFs in a model of DC-mediated immune response. We found that non-toxic concentrations of CNFs impaired the differentiation, and subsequent maturation of huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 63 publications
3
49
2
Order By: Relevance
“…Overall, the NFCs under study did not impair the cell viability of dermal, lung or macrophage cells. This is in accordance with previous in vitro studies showing that NFC gels are non- cytotoxic for a wide range of cells, including dendritic cells, macrophages, fibroblasts, keratinocytes, human cervic carcinoma and hepatoma cell lines [1315, 28]. Moreover, NFC gels, aerogels and membranes were proven to be biocompatible when evaluated for diverse tissue engineering and biomedical applications [12, 18, 3033].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Overall, the NFCs under study did not impair the cell viability of dermal, lung or macrophage cells. This is in accordance with previous in vitro studies showing that NFC gels are non- cytotoxic for a wide range of cells, including dendritic cells, macrophages, fibroblasts, keratinocytes, human cervic carcinoma and hepatoma cell lines [1315, 28]. Moreover, NFC gels, aerogels and membranes were proven to be biocompatible when evaluated for diverse tissue engineering and biomedical applications [12, 18, 3033].…”
Section: Discussionsupporting
confidence: 90%
“…As also observed by Tomic et al [28], the agglomeration of U-NFC did not significantly change when comparing cell culture medium and phosphate buffer suspensions, showing the presence of small agglomerates in both conditions. The type, amount and conformation of the adsorbed proteins will be influenced by the nanofibre surface chemistry among other nanomaterials properties.…”
Section: Discussionsupporting
confidence: 82%
“…Such a wide application spectrum is related mainly to their nanometer-sized features, large surface area, specific biomechanical characteristics, surface chemistry, ease of conjugation, high biocompatibility, and low (if any) cytotoxicity (Alexandrescu et al 2013) with tolerogenic potential to the immune system (Tomić et al 2016). Due to a general acceptance as˝biosafe˝nanomaterial (Č olić et al 2014;Tomić et al 2016), the cellulose nanocrystals (CNCs), with typical sizes of \300 nm in length and around 10 nm in diameter (Habibi et al 2010), have also been readily evaluated as catalysis (Zhou et al 2013) in biomedical engineering (Sinha et al 2015), as well as targeted drugs (Taheri & Mohammadi 2015) and gene (Hu et al 2015) delivery. Recent studies also demonstrated the potential of CNCs to target tumours via the Enhanced Permeability and Retention (EPR) effect and delivery of organic compounds or drugs into cancer cells (Drogat et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The pristine CNFs can induce active immune tolerance, enabling treatment of exaggerated inflammatory conditions threatening to destroy host tissue and support of wound healing [71]. In addition, oxidized CNF gels could act as pH responsive structures, which may have applications in dressings for chronic wounds.…”
Section: Topical Administrationmentioning
confidence: 99%
“…Because of the relatively low rigidity of CNFs as a result of the alternating crystallinity, they are more often used in biomedical applications compared with CNCs [71].…”
Section: Applicationsmentioning
confidence: 99%